Bilateral Obstructive Uropathy Caused by Congenital Bladder Diverticulum Presenting as Hypertensive Retinopathy - Kim, San (J Korean Med Sci, 2018)
A congenital bladder diverticulum (CBD) is caused by inherent muscular weakness instead of obstruction of the bladder outlet. The major clinical conditions are recurrent urinary tract infection (UTI) and voiding dysfunction. This report describes a 15-year-old male adolescent who developed sudden visual disturbance resulting from hypertensive retinopathy. The cause of hypertension was bilateral obstructive uropathy caused by enlarged paraureteral bladder diverticula. After the non-functioning right kidney and ureter and the bilateral diverticula were removed, the left ureter was reimplanted in the bladder. Pathologic findings showed chronic pyelonephritis and partial loss of the bladder musculature in the diverticular wall. This observation indicates that dilated CBD can cause latent UTI, ureteral obstruction, hydronephrosis, and secondary hypertension.